Factors Causing Destructive Fishing in the Waters of the West Seram Sea - Hehanussa, D. J. A; Lewerissa, Yanti Amelia; Hattu, Jopy; Tuhumury, Carolina (GoAcademica Research & Publishing, 2024)
The use of fishing gear that is not environmentally friendly, which has led to the emergence of destructive fishing activities, is still carried out by fishing communities around the waters of West Seram. The aim of this research is to examine and analyze policies for dealing with the use of non-environmentally friendly fishing gear in the fisheries sector in West Seram Waters. The research method in this research is normative legal research equipped with a socio-legal approach. The approach used in this research is a statutory approach and a conceptual approach. The data collection technique is a literature study and is complemented by field data obtained through observation and in-depth interviews with stakeholders. Next, the data was analyzed qualitatively. The research results show that the fishing communities in Hatusua Village, Kamal Village and Waisarisa Village, which are located around the West Seram Waters, often use fishing gear that is not environmentally friendly when catching fish. The factors that cause them to carry out destructive fishing are factors such as a fairly long span of control making supervision difficult, economic needs; very simple fishing gear; providing assistance is not on target; Pokmaswas are less empowered; and lack of supervision between institutions. Meanwhile, countermeasures to overcome destructive fishing can be carried out through penal and non-penal approaches.